MAHMUD AZ-ZAMAXSHARIYNING MA’NAVIY-MA’RIFIY FAOLIYATI - Raxmedova, M.A. (SCIENCE and SOCIETY, 2023)
This article analyzes the life and work of az-Zamakhshari from the point of view of the pedagogical content of the spiritual heritage, who in his youth constantly traveled from city to city, from country to country in order to acquire knowledge and science, talked with contemporary sheikhs and scientists, sharply criticized ignorance and illiteracy.
Keywords: learning; scientific discussions; worldview; humility and manners; perseverance and patience; pleasure; science of interpretation; education; science; ignorant; spiritual and educational; cultural life; political subject; religious; political conflicts; public officials